Multiple-locus variable-number tandem-repeat analysis of Streptococcus pneumoniae and comparison with multiple loci sequence typing - van Cuyck Hélène (BMC Microbiology, 2012)
Abstract Background Streptococcus pneumoniae infections remain a major cause of morbidity and mortality worldwide. The diversity of pneumococci was first evidenced by serotyping of their capsular polysaccharides, responsible of virulence, resolving into more than 93 serotypes. Molecular tools have been developed to track the emergence and the spread of resistant, hyper virulent or non-vaccine type clones, particularly DNA-based methods using genetic polymorphism. Pulsed-Field Gel Electrophoresis analysis (PFGE) and Multiple Loci Sequence Typing (MLST) are the most frequently used genotyping techniques for S. pneumoniae. MLST is based on sequence comparison of housekeeping genes clustering isolates within sequence types. The availability of genome sequence data from different S. pneumoniae strains facilitated the search for other class of genetic markers as polymorphic DNA sequences for a Multiple-Locus Variable-Number Tandem-Repeat Analysis (MLVA). This study aims at confirming the relevance of MLVA of S. pneumoniae, comparing MLST and MLVA performances when discriminating subgroups of strains belonging to the same Sequence Type (ST), and defining a restricted but universal set of MLVA markers that has at least the same discriminatory power as MLST for S. pneumoniae by applying marker sets used by different authors on 331 isolates selected in UK. Results A minimum spanning tree was built including the serotypes distribution and comparing MLVA and MLST results. 220 MLVA types were determined grouped in 10 Sequence Types (ST). MLVA differentiated ST162 in two clonal complexes. A minimal set was defined: ms 25 and ms37, ms17, ms19, ms33, ms39, and ms40 including two universal markers. The selection was based on MLVA markers with a Diversity Index >0.8 and a selection of others depending of the population tested and the aim of the study. This set of 7 MLVA markers yields strain clusters similar to those obtained by MLST. Conclusions MLVA can discriminate relevant subgroups among strains belonging to the same ST. MLVA offers the possibility to deduce the ST from the MLVA Type. It permits to investigate local outbreaks or to track the worldwide spread of clones and the emergence of variants.